PROSEDUR PEMBELIAN DAN PENERIMAAN BARANG FOOD AND BAVERAGE DEPARTMENT PADA HOTEL SALAK THE HERITAGE - , ISTIARA DYAH UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the tourism industry, especially in the field of hospitality purchasing department is one that plays an important role in the development of the hotel. Purchasing is part of the hotel department is in charge of purchasing items requested in a department in a hotel is no exception Food And Bverage department. Therefore, the need for analytical procedures and acceptance of goods purchases Food And Baverage. The purpose of this analysis is to determine what are the necessary forms, what are the relevant parts in the process, how the procedure of purchase and receipt of goods, as well as any problems that occur. The method used is documentation, observation, and interviews. After all the data collected will then be analyzed and then made a chart that explains the procedure of purchase and receipt of goods Food And Baverage by the Purchasing Department. The results of this analysis indicate that the procedure of purchase and receipt of goods Food And Baverage running properly and in accordance with existing procedures.